Using Scrabble as a Gamification to Enhance Students’ Motivation and Vocabulary Acquisition: Teachers’ Perspective - Sholihatul Hamidah Daulay; Devika Adelita (Universitas Tidar, 2023)
Technology has aided in the development of learning media with a variety of media creations as media for students to be more engaged in learning to use a laptop or smartphone with Android capability by installing the application in question. In this study, the use of games or gamification applications in learning English, specifically digital scrabble games, is discussed. This study attempts to investigate the use of scrabble to support students' motivation and vocabulary acquisition based on teachers' perspectives. The subjects for this research were 12 (twelve) English teachers of North Sumatera. In conducting this research, the researcher used the case study methodology. The data were collected through an open questionnaire requiring a lengthy response from the respondent and a closed questionnaire with an alternative answer decided by the questionnaire's creator, namely yes or no. The results showed that, in accordance with the teachers' perceptions, utilizing scrabble can motivate students to study because they become interested, feel challenged while using it, and want to keep playing. Due to the students' ability to learn and assimilate new words through scrabble, their vocabulary acquisition also enhanced.